2009
DOI: 10.1179/102453309x385179
|View full text |Cite
|
Sign up to set email alerts
|

Management of transfusional iron overload in Latin America: current outlook and expert panel recommendations

Abstract: The results of a meeting of physicians convening in Latin America to develop expert opinions on the diagnosis, monitoring and treatment of iron overload are as follows. An accurate diagnosis can be obtained by neonatal screening for haemoglobinopathies, especially sickle cell disease and the thalassaemias. Disease-specific registries are needed to demonstrate the extent of the problem to health authorities. Disparities in the quantity and quality of blood products must be addressed, and uniform transfusion gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…It may decline when a long‐term cancer remission state has been achieved. Our data support existing recommendations advocating lower thresholds for screening of multitransfused patients with cancer with a lifetime transfusion burden of ≥10 RBC units starting from serum ferritin levels of >500 μg/L during follow‐up .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It may decline when a long‐term cancer remission state has been achieved. Our data support existing recommendations advocating lower thresholds for screening of multitransfused patients with cancer with a lifetime transfusion burden of ≥10 RBC units starting from serum ferritin levels of >500 μg/L during follow‐up .…”
Section: Discussionsupporting
confidence: 83%
“…Guidelines are available in countries outside the U.S., but in the U.S. the only extant guidelines are the Children's Oncology Group Long‐Term Follow‐Up Guidelines, which do not address TRIO outside the hematopoietic stem cell transplantation (HSCT) setting and are developed for childhood cancer survivors. Although most guidelines recommend treatment in patients with a life expectancy of >1 year and a lifetime transfusion burden of ≥10–20 RBC units, serum ferritin levels >1,000–2,500 μg/L, and/or liver iron content (LIC) ≥7 mg Fe/g dry weight (dw), some guidelines advocate early assessment and treatment after transfusion of 8 RBC units, serum ferritin levels >500 μg/L, or LIC >2–3 mg Fe/g dw . Other guidelines also include transfusion dependence of ≥2.0 RBC units per month as a trigger for initiation of iron chelation therapy .…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, the retrospective RELATH study in Latin America, using SF as a marker of iron overload, demonstrated that iron overload and related complications are significant clinical problems in this region as well; hepatic complications were found in 65.3% of the patients, followed by cardiac (27.5%) and endocrine complications (18.2%) [6]. The diagnosis [7] and monitoring of iron overload may improve in the region if SF is complemented with the MRI of the liver and heart [8]. Therefore, to assess the prevalence of iron overload accurately using liver and cardiac MRI, ASIMILA (assessment of iron overload in transfusion-dependent patients by MRI in Latin America) study was conducted in transfusion-dependent patients with chronic anemias with the exception of thalassemia.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, iron chelation may be useful therapeutic strategy in AMD. This is supported by the reports on usefulnes of such strategy in some neurological diseases, including Alzheimer disease and Parkinson disease, and Huntington disease and Friedrich ataxia (82)(83)(84)(85).…”
Section: Perspectivementioning
confidence: 54%